Metformin inhibits the prometastatic effect of sorafenib in hepatocellular carcinoma by upregulating the expression of TIP30. Issue 4 (23rd February 2016) - Guo, Zhigui; Cao, Manqing; You, Abin; Gao, Junrong; Zhou, Hongyuan; Li, Huikai; Cui, Yunlong; Fang, Feng; Zhang, Wei; Song, Tianqiang; Li, Qiang; Zhu, Xiaolin; et al.
Abstract : We previously found that a low dose of sorafenib had a prometastatic effect on hepatocellular carcinoma (HCC), which was caused by downregulation of TIP30 expression. More recently, metformin has been shown to have potential as a preventive and therapeutic agent for different cancers, including HCC. This study evaluated whether the combination of sorafenib and metformin is sufficient to revert the expression of TIP30, thereby simultaneously reducing lung metastasis and improving survival. Our data show that the combination of sorafenib and metformin inhibits proliferation and invasion in vitro, prolongs median survival, and reduces lung metastasis of HCC in vivo . This effect is closely associated with the upregulation of TIP30, partly through activating AMP‐activated protein kinase. Thioredoxin, a prometastasis factor, is negatively regulated by TIP30 and plays an essential role during the process of HCC metastasis. Overall, our results suggest that metformin might be a potent enhancer for the treatment of HCC by using sorafenib. Abstract : Our study is conducted to evaluate whether the combination of sorafenib and metformin is sufficient to revert the expression of TIP30, by which reducing the lung metastasis and improving the survival simultaneously. Our data show that the combination of sorafenib and metformin inhibits proliferation and invasion in vitro, prolongs the median survival and reduces lung metastasis of HCC in vivo. This effect is closely associated with the up‐regulation of TIP30, partly through activating AMPK.